Evaluasi Response Time Pelayanan terhadap Kepuasan Pasien di Ruang PONEK - Dyah Puji Astuti; Sumarni Sumarni; Juni Sofiana (Jurnal Ilmiah Kesehatan, 2025)
Patient satisfaction is an important indicator for assessing the quality of health services, particularly ain obstetric and neonatal emergency care at the PONEK unit. Response time in sevices deliver is one of the critical factors influencing patients satisfaction. The objective is to examine the relationship between service response time and the level of patient satisfaction at the PONEK unit of PKU Muhammadiyah Gombong Hospital. This study employed a coreelation analytic dsign with a cross-sectional approach. The population included all patients admitted to the PONEK unit and 45 respondents were recruited using accidental sampling. Data were analyzed to assess the association between response time ant patien satisfaction. The result showed a significant relationship between response time and patient satisfaction (p<0,000). It can be concluded that the faster the servise response time the higher the level of patien satisfaction.